Signaling networks in immunometabolism - Saravia, Jordy; Raynor, Jana L.; Chapman, Nicole M.; Lim, Seon Ah; Chi, Hongbo (Cell research, 2020)
Adaptive immunity is essential for pathogen and tumor eradication, but may also trigger uncontrolled or pathological inflammation. T cell receptor, co-stimulatory and cytokine signals coordinately dictate specific signaling networks that trigger the activation and functional programming of T cells. In addition, cellular metabolism promotes T cell responses and is dynamically regulated through the interplay of serine/threonine kinases, immunological cues and nutrient signaling networks. In this review, we summarize the upstream regulators and signaling effectors of key serine/threonine kinase-mediated signaling networks, including PI3K–AGC kinases, mTOR and LKB1–AMPK pathways that regulate metabolism, especially in T cells. We also provide our perspectives about the pending questions and clinical applicability of immunometabolic signaling. Understanding the regulators and effectors of immunometabolic signaling networks may uncover therapeutic targets to modulate metabolic programming and T cell responses in human disease.